MANAGEMENT OF INNOVATION IN LANGUAGE TEACHING (A CASE STUDY OF MANAGING INNOVATION IN RURAL SCHOOLS IN NTT PROVINCE, INDONESIA) - Santri E. P. Djahimo (Celt: A Journal of Culture, English Language Teaching & Literature, 2015)
This writing is about management of innovation in language teaching and it is reflected by a case study of managing innovation in rural schools in East Nusa Tenggara (NTT) Province, Indonesia. The content of this writing mostly discusses about how to manage innovation in language teaching. However, there are several minor parts describe about the case study conducted in rural schools in Nil Province. Innovation in education is not a totally new thing to be discussed. Many researchers as well as writers have given great attention to this topic for many years. Innovation in this study means a new way of doing something to make an improvement to someone or something. In this case, an innovation in the form of teaching methodology has been implemented to create a better atmosphere in the classroom and an improvement in the students1 performance in vocabulary acquisition in EFL classroom. It has been expected that through this innovation, the students' performance would be better in vocabulary acquisition and so a better output could be achieved. Through this writing, the writer would like to show that educational innovation needs to be applied, especially by those who want better changes in order to improve themselves and achieve better results in education. The success and failure of this kind of innovation will be determined by several essential factors included in the three big category, namely Knowledge and Skill factors; Resource and Support factors; and Human and Social factors, as well as characteristics and attributes. These factors determine whether or not an innovation in education can be adopted.